x = y² подставим это во второе уравнение:
2y² - y - 3 = 0,
D = (-1)² - 4*(-3)*2 = 1+24 = 25 = 5²
y = (1±5)/(2*2) = (1±5)/4
y₁ = (1-5)/4 = -4/4 = -1 или y₂ = (1+5)/4 = 6/4 = 3/2.
1) если y₁ = -1 тогда x₁ = (-1)² = 1. Первая точка (x₁; y₁) = ( 1; -1).
2) если y₂ = (3/2) = 1,5 тогда x₂ = (3/2)² = 9/4 = 2,25. Вторая точка
(x₂; y₂) = ( 2,25; 1,5).
Ответ. ( 1; -1), ( 2,25; 1,5).
Х+8=15
х=15-8
х=7
6+9=х
х=15
7+х=21
х=21-7
х=14
Это уравнение
Лутвилчоциыичдщцицмовщалвтут
Поділимо почленно:n+2+8/n
Тоді n=1,2,4,8.